Improving Students’ Language Learning through Project-Based Learning Activities - Yewande Ukah; Christian Ayewu; Priscilla Oworu (Universitas Muhammadiyah Barru, 2023)
This current research aims to (1) find out the improvement of score and quality of students’ project task through project-based learning activities in English classroom, (2) analyze students’ activities in carrying out the project-based learning, and (3) analyze students’ attitudes in English learning through the project-based learning model. This classroom action research was conducted in Isanbi Comprehensive High School at Ilisan-Remo, Nigeria. The research participants were 19 first grade students. They were students who had a lot of problems with the value of project assignments, where the average value they got in the second semester of the 2021/2022 academic year was only 70.42, which belonged to the sufficient category because it did not reach the standard of good category (75). From the result of the research conducted in 2 cycles, it was found that in each cycle there was an average increase with a deviation of 9.27 and increased to the good category. Thus, the researchers concluded that students’ language learning can be improved through project-based learning activities in the first grade junior high school students.